Using Grammarly as a Tool to Improve the Students’ Grammatical Accuracy in Translation - Rudy Sofyan; Dea Yuanita Nasution (English Language and Literature, 2023)
Even though there are many translation aids such as online machine translation and online dictionaries that help the students in translating text from Bahasa Indonesia into English, they are not enough to make sure that the students’ translation is grammatically correct. Based on such reasons, this study aims to explore the effect of using Grammarly application as a translation tool to improve the students’ translation quality. By checking the students’ translation using Grammarly, it is found that the most common grammatical mistakes made by students are the improper use of space, misspelling, improper use of articles, tenses, and wordy words. Besides, it is also found that Grammarly has many strengths, such as: accuracy in identifying orthography issues, concern towards the wordy diction, consistency in using a certain English variant, providing its users with their personal dictionary, providing constructive feedback, and accessible in many platforms. Meanwhile, the weaknesses of Grammarly include over checking on people’s name spelling, misleading feedback, inconsistency in identifying mistakes, limited explanation, questionable “Grammar Checker”, and working just like a machine. The conclusion is Grammarly will be an excellent translation tool to improve students’ translation quality if accompanied by the students’ sufficient background skill and knowledge.